Prerequisites and retrospective formation of financial intelligence of Ukraine - Kolodiychuk, Oleksandr; Karapetyan, Olha; Rudyi, Roman (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
The article defines the retrospective features of the formation of financial intelligence in the prevention of legalization of illegal income, the study of theoretical aspects of its activity in the observance of national security. In particular, the main periods of the historical process of the establishment of the financial intelligence institute in Ukraine are outlined. It was determined that the organizational formation of the financial intelligence subsystem is based on the following groups of prerequisites: historical, essential and functional. Scientific approaches to determining the categorical content of financial intelligence are substantiated. The essence of financial intelligence has been studied and it has been established that it is inextricably linked to combating the legalization of proceeds of crime and the financing of terrorism. Financial intelligence is by definition interdisciplinary. It manifests itself in its ambiguity and multifacetedness. It is studied not only from the point of view of finance, public administration, audit, economic security, but also, of course, financial law. It was established that the State Financial Monitoring Service of Ukraine is the central national body responsible for collecting, analyzing and transferring data on suspicious financial transactions to the competent authorities. It was determined that financial intelligence is considered from two positions: as a science, it is a set of ideas and views on the process of obtaining knowledge as a result of searching and obtaining information about illegal acts, which reflects the properties of objects and their interaction in solving research tasks in the mind of the subject , knowledge and as a type of practical activity is the way the subject of the financial intelligence unit uses the properties of objects and the relationships between them in solving the problems of countering the legalization of income obtained illegally or the financing of terrorism. It has been established that the object of financial intelligence is actions with assets related to the relevant participants of financial transactions that carry them out, provided there are risks that arise during the use of these assets for the purpose of legalizing income obtained through criminal means or financing terrorism. It has been determined that one of the effective forms of responding to the challenges of the criminal environment is to conduct research, expose and publicize schemes by which criminal income is given a legal appearance and terrorism is financed. The need to carry out such work is directly provided for by the legislation of Ukraine and FATF international standards. Prospective directions for the development of financial intelligence are: maximum automation of operational and strategic analysis processes; establishment of e-channels for rapid communication with law enforcement agencies; improvement of the financial investigation procedure regarding the latest technologies.